3D DIGITIZATION OF MUSEUM ARTEFACTS WITHIN THE INTERREG IRON AGE DANUBE PROJECT - M. Vuković; J. Balen; H. Potrebica; M. Mađerić; V. Španiček (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2022)
Iron Age Danube project dealt with a wide variety of topics and sites dating back to the Iron age along the Danube river. Primary goals set by the Archaeological museum in Zagreb were the creation of a cultural route for the site of Kaptol, presentation of the site itself and digitization of artefacts from the necropolis of Kaptol – Čemernica. The latter were a part of the permanent museum exhibition in the Iron age section at the Archaeological museum in Zagreb. This paper will present the workflow used to generate image-based 3D models of more than 100 artefacts. The museum itself doesn’t have a digitization laboratory or allocated space, a problem which was encountered in other cultural heritage digitization projects, which meant that the setup had to be quickly assembled and disassembled as needed. This paper will present the problems encountered during the entire process, from image acquisition to data processing, as well as the potential solutions. For the purposes of the project we used Agisofts Metashape software which at the time required masks for all photographs involved in the image-based modelling process, in a turntable static camera setup. The newer versions of the software have two additional options one of which ignores the surrounding reference points and uses the markers generated by Metashape to complete the initial camera alignment. The sheer amount of artefacts we aimed to digitize meant that we had to streamline the process of acquiring and processing the photographs and their respective masks. This process was meticulously documented and optimized to take the least possible time while obtaining a satisfactory level of detail on the resulting 3D model. Although the new versions of the software dispense with the need for masking the photographs, the process of removing the unwanted points from the point cloud and aligning different chunks can also be time consuming. This paper will present our results with various photo alignment methods and try to provide an objective comparison. We will also explore the possibilities of utilizing the finished models in computer generated reconstructions of sites, and their usability in promoting the museum and potential exhibitions. Finally, the paper will assess the value of digitizing larger parts of museum collections in light of the recent earthquake in Zagreb which seriously damaged most of the artefacts in the museum.